Investigation of anti-neuronal antibodies and disparity in central hypersomnias - Prochazkova, Petra; Sonka, Karel; Roubalova, Radka; Jezkova, Janet; Nevsimalova, Sona; Buskova, Jitka; Merkova, Radana; Dvorakova, Tereza; Prihodova, Iva; Dostalova, Simona; Tlaskalova-Hogenova, Helena (Sleep medicine, 2024)
STUDY OBJECTIVES: Microbial antigens can elicit an immune response leading to the production of autoantibodies cross-reacting with autoantigens. Still, their clinical significance in human sera in the context of brain diseases is unclear. Therefore, assessment of natural autoantibodies reacting with their neuropeptides may elucidate the autoimmune etiology of central hypersomnias. The study aims to determine whether serum autoantibody levels differ in patients with different types of central hypersomnias (narcolepsy type 1 and 2, NT1 and NT2; idiopathic hypersomnia, IH) and healthy controls and if the differences could suggest the participation of autoantibodies in disease pathogenesis. METHODS: Sera from 91 patients with NT1, 27 with NT2, 46 with IH, and 50 healthy controls were examined for autoantibodies against assorted neuropeptides. Participants were screened using questionnaires related to sleep disorders, quality of life, and mental health conditions. In addition, serum biochemical parameters and biomarkers of microbial penetration through the intestinal wall were determined. RESULTS: A higher prevalence of autoantibodies against neuropeptides was observed only for alpha-melanocytes-stimulating hormone (α-MSH) and neuropeptide glutamic acid-isoleucine (NEI), which differed slightly among diagnoses. Patients with both types of narcolepsy exhibited signs of microbial translocation through the gut barrier. According to the questionnaires, patients diagnosed with NT2 or IH had subjectively worse life quality than patients with NT1. Patients displayed significantly lower levels of bilirubin and creatinine and slightly higher alkaline phosphatase values than healthy controls. CONCLUSIONS: Overall, serum anti-neuronal antibodies prevalence is rare, suggesting that their participation in the pathophysiology of concerned sleep disorders is insignificant. Moreover, their levels vary slightly between diagnoses indicating no major diagnostic significance.
Keywords: Disorders of Excessive Somnolence; Humans; lidé; Quality of Life; Narcolepsy; autoprotilátky; poruchy nadměrné spavosti; kvalita života; neuropeptidy; Neuropeptides; Autoantibodies; narkolepsie